Validity of ferritin as a predictor of severe dengue in children - Kadek Adi Suryamulyawan; I Nyoman Budi Hartawan; I Wayan Gustawan; Ida Bagus Gede Suparyatha; Dyah Kanya Wati; I Made Gede Dwi Lingga Utama; Siska Permanasari Sinardja; I Made Yullyantara Saputra; Putu Andrie Setiawan (Medical Faculty of Brawijaya University, Indonesia, 2026)
Background: Dengue infection is a significant global health problem, particularly in tropical and subtropical regions, where severe dengue cases carry high morbidity and mortality. Ferritin levels, an acute-phase reactant and marker of iron storage, have been evaluated as a potential biomarker for predicting severe dengue infection. This study aimed to evaluate the validity of ferritin as a predictor of severe dengue in children. Methods: This diagnostic study was conducted at Ngoerah Hospital, Denpasar, from January to June 2025, recruiting 69 children based on WHO criteria through consecutive sampling. Ferritin levels were measured using ELISA and analyzed using SPSS version 26 using bivariate tests, ROC analysis, and diagnostic parameter calculations. Results: A total of 69 children with dengue infection were involved (mean age 10.09 years). The mean serum ferritin level in all patients was 4820.97±6327.75μg/L. In the severe dengue group, the mean ferritin level was 6973.75±9089.48 μg/L, while in the mild dengue group it was 3672.82±3849.37μg/L, with a mean difference of 3300.93 μg/L (95% CI: 187.10–6414.76; p=0.190). ROC curve analysis showed an AUC of 0.596 (95% CI: 0.454–0.739; p=0.190) with an optimal cut-off point at 880.9450 μg/L (sensitivity 83.33%; specificity 31.11%. Diagnostic evaluation showed an accuracy of 49.28%, a positive predictive value (PPV) of 39.22%, a negative predictive value (NPV) of 77.78%, a positive likelihood ratio (PLR) of 1.21, a negative likelihood ratio (NLR) of 0.54, and a DOR of 2.24 (0.65–7.85). Conclusion: Ferritin levels can be a predictor of diagnosis in children infected with severe dengue.